Legal status of abiotic resources in outer space: Appropriability, ownership, and access. (31st December 2022) - Su, Jinyuan
Abstract: Humankind's exploration and use of outer space are first and foremost limited by the obligation of non-appropriation. This prohibition, with an aim to prevent conflicts arising from competing territorial claims, does not extend to the exploitation of abiotic resources in space. Recent state practice has shown a clear trend of regarding such exploitation as a freedom of exploration and use of outer space. The future international legal regime should prohibit property claims over natural resources in place on celestial bodies, avoid the controversial issue of ownership, co-ordinate the resource activities of different entities by a stage-specific and priority-right-based mechanism, and harden the obligations of capacity-building and co-operation. The ideas of parallel system and monetary benefit sharing should not be discarded although resistance from major space-faring countries is foreseeable.